Nanofocusing of circularly polarized Bessel-type plasmon polaritons with hyperbolic metamaterials. Issue 2 (6th February 2017) - Liu, Ling; Gao, Ping; Liu, Kaipeng; Kong, Weijie; Zhao, Zeyu; Pu, Mingbo; Wang, Changtao; Luo, Xiangang
Abstract : An evanescent Bessel beam with a lateral dimension beyond the diffraction limit is generated by combining plasmonic metasurfaces and hyperbolic metamaterials. Abstract : A miniature evanescent Bessel beam generator is realized by utilizing the combination of metasurfaces based on a concentric grating and hyperbolic metamaterials composed of alternate metal/dielectric multilayers. After introducing the plasmonic cavity lens, the feature size could be compressed to 62 nm (0.17 λ 0 ) at the wavelength of 365 nm with a working distance as large as 100 nm. The theoretical models are verified by a set of experiments, providing a promising way to control light at the nanoscale.